Secular–religious competition in Western democracies: 1990 to 2014. Issue 2 (3rd May 2016) - Fox, Jonathan
Abstract: While secularization theory—the prediction that religion is in decline—is itself in decline, many argue that it is still applicable to the West. I argue that rather than causing religion's decline, modernity has caused the rise of secularism as an ideology that competes with religion. I test this proposition—which I call the secular–religious competition perspective—by measuring change over time in 117 distinct government religion policies in 27 Western democracies between 1990 and 2014 using the Religion and State round 3 (RAS3) dataset. I find that while, overall, governments have added new policies, especially those limiting the religious institutions and practices of religious minorities, overall 96 policies were added and 31 dropped. Also, all but two Western democracies changed their religion policy in some manner during this period. This better reflects a religious economy where secular and religious political forces compete to influence government religion policy than one where religion is in decline.